School-based delivery of a dialogic book sharing intervention: a feasibility study of Books Together - Williams, Margiad E.; Owen, Claire; Hutchings, Judy (Frontiers in Education, 2024)
Growing numbers of children enter mainstream education without the skills needed to prosper in the school environment. Without additional support, these children face poor long-term outcomes in terms of academic attainment, mental health difficulties and social problems. The aim of this study was to investigate the feasibility and acceptability of school-based delivery of the Books Together dialogic book sharing program to groups of parents, and to explore whether it impacts parent and child outcomes in order to facilitate school readiness. Parents of children aged 3-5 years old (n =16) were recruited from four North Wales primary schools. Video observations of parent/child interactions, a gaming format measure of expressive child language ability, parent-report measures of children's behavior, and social-emotional ability and of their parental competence were collected preand post-intervention. Thematic analysis of interviews with parents and the school-based staff who delivered the program explored feasibility and acceptability of the program. Significant postintervention increases in observed positive parenting and child expressive language skills and significant reductions in observed negative parenting were found. Parents reported significantly higher rates of child prosocial behavior and social/emotional ability as well as improved parenting competency at follow-up. Thematic analysis showed that staff and parents were satisfied with the program and that it was feasible to deliver in a school environment. The Books Together program is a low-cost intervention that, when delivered by school-based staff, shows promise for increasing the use of parenting strategies that build children's language and social/emotional skills associated with school readiness.